Frequency and Pattern of Dyslipidemia in Patient Presenting with Type II Diabetes at Tertiary Care Hospital - Asmat, Fauzia; Hanif, Shamimah; Abdul Malik; Ahmad, Sarfraz; Shah, Zaheer; Shah, Mir Usman; Syed Ehsanullah; Kakar, Sana Ullah (Indus Journal of Bioscience Research, 2025)
Background: Dyslipidemia is a major modifiable cardiovascular risk factor frequently seen in type II diabetes mellitus (T2DM) due to insulin resistance and poor glycemic control. This study investigates the frequency and pattern of dyslipidemia in T2DM patients at a tertiary care hospital. Objective: to ascertain the distribution and prevalence of dyslipidemia in individuals with type II diabetes and investigate its correlation with age, gender, HbA1c levels, and diabetes duration. Methodology: 150 individuals with a diagnosis of type 2 diabetes participated in a cross-sectional study. Lipid profiles, HbA1c values, and the length of diabetes were all gathered. Individuals with concomitant lipid problems or those undergoing lipid-lowering medication were not included. Results: The most common anomaly was low HDL-C (69.3%), which was followed by hypertriglyceridemia (60.7%) and high LDL-C (65.3%). Patients with prolonged disease duration and poor glycemic control were more likely to have dyslipidemia. Conclusion: In patients with type 2 diabetes, dyslipidemia is quite common and closely linked to both the length of diabetes and poor HbA1c control. To lower cardiovascular risk, early screening and comprehensive management are crucial.